The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.cca.2019.03.1365
|View full text |Cite
|
Sign up to set email alerts
|

Commutability of a whole-blood external quality assessment material for point-of-care C-reactive protein, glucose, and hemoglobin testing

Abstract: BACKGROUND: The optimal situation in external quality assessment (EQA) is to use commutable materials. No previous study has examined the commutability of a whole-blood material for point-of-care (POC) testing. The aim of this study was to determine the commutability of the Norwegian Quality Improvement of Laboratory Examinations (Noklus) organization's "in-house" whole-blood EQA material for C-reactive protein (CRP), glucose, and hemoglobin for frequently used POC instruments in Norway and to determine the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…41 Commutability relates to the ability of the analyzer to provide measurement results using such quality control materials that, in a method comparison, show the same relationship as, for example, using standard samples (eg, human blood panels). This is not always the case, as recently published by Bukve et al, 42 so that the POCT12-A3 recommendation to assess the commutability of such material should be acknowledged.…”
Section: Discussionmentioning
confidence: 96%
“…41 Commutability relates to the ability of the analyzer to provide measurement results using such quality control materials that, in a method comparison, show the same relationship as, for example, using standard samples (eg, human blood panels). This is not always the case, as recently published by Bukve et al, 42 so that the POCT12-A3 recommendation to assess the commutability of such material should be acknowledged.…”
Section: Discussionmentioning
confidence: 96%
“…Commutability assessments of the three EQA materials were first performed using the CLSI EP30‐A approach, which analyzes samples with the pair MPs and determines if the materials fall within the 95% PI. Bukve et al 31 recently demonstrated that whole‐blood EQA material was commutable on three POC glucose instruments using this approach. Our study showed that HWBs were commutable on all five POC instruments at all three concentrations analyzed, while CCMs and PHSs were commutable on one and two instruments at all three levels, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The results also displayed good linear correlation in each comparison.Commutability assessments of the three EQA materials were first performed using the CLSI EP30-A approach, which analyzes samples with the pair MPs and determines if the materials fall within the 95% PI. Bukve et al31 recently demonstrated that whole-blood EQA material was commutable on three POC glucose…”
mentioning
confidence: 99%
“…The commutability is a property required to provide an EQAS program classified as category 1 or 2, and without proven commutability the key benefit of assessment of traceability of the result to a reference system is lost, 36 as shown by comparing the results obtained from traditional schemes using both serum matrix control materials 37,38 and whole‐blood control materials 39 . The commutability of some whole‐blood EQAS control materials has been recently evaluated using the new IFCC approach, pursued for point of care testing, including only Hb as hematologic parameter 35‐40 . Conversely, at least to our knowledge, the commutability property of control materials used for hematologic analyzers alignment is not usually verified.…”
Section: Discussionmentioning
confidence: 99%